Korelasi keterampilan membaca pemahaman dengan kemampuan menyelesaikan soal cerita pecahan pada peserta didik kelas V sekolah dasar - Asna Mu'afatika Khoirul Nikmah; Riyadi Riyadi (Universitas Sebelas Maret, 2025)
This research aims to investigate the existence of a significant positive correlation between reading comprehension skills and the ability to solve word problems involving fractions among fifth-grade elementary school students in Ngemplak District, Boyolali. The study adopts a quantitative research design with a correlational approach. The sample consisted of 82 student. Data collection was conducted utilizing two distinct test instruments: a multiple-choice test to measure reading comprehension skills, developed based on Barrett’s taxonomy indicators, and an essay-type test designed to assess the problem-solving ability related to fraction word problems structured according to Polya’s problem-solving steps. The prerequisite test included normality and linearity tests. The hypothesis testing was conducted using Pearson’s product moment simple correlation. The result indicated a significant positive correlation between reading comprehension skills and the ability to solve fraction word problems. This finding is evidenced by the simple correlation test, which showed a significance value of 0.000 < 0.05 and a correlation coefficient of 0,596, indicating a moderate level of correlation. Furthermore, the coefficient of determination was 0,352, implying that reading comprehension skills contribute 35,2% to the ability to solve fraction word problems.